Solving the fermionic mass hierarchy of the Standard Model - Abbas G. (My University, 2025)
We show that a simultaneous explanation for fermionic mass hierarchy among and within the fermionic families, quark-mixing, can be obtained in an extension of the Standard Model, with real singlet scalar fields, which are UV completed by vector-like fermions and a strongly interacting sector. © 2019 World Scientific Publishing Company.